2013
DOI: 10.1093/infdis/jit105
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Modified Vaccinia Ankara in Hematopoietic Stem Cell Transplant Recipients: A Randomized, Controlled Trial

Abstract: NCT00565929.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…As has been reported in other clinical studies evaluating MVA [1013, 1518] or first- and second-generation live smallpox vaccines [14], the total antibody response is higher, both in terms of the number of responders and in the magnitude of the response, compared with neutralizing antibody titers. Although neutralizing antibodies are considered an important immunological correlate of protection [22], other antibody functions such as complement fixation, antibody directed cellular cytotoxicity, and opsonization have been shown to play an important role in protection as well [2327].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As has been reported in other clinical studies evaluating MVA [1013, 1518] or first- and second-generation live smallpox vaccines [14], the total antibody response is higher, both in terms of the number of responders and in the magnitude of the response, compared with neutralizing antibody titers. Although neutralizing antibodies are considered an important immunological correlate of protection [22], other antibody functions such as complement fixation, antibody directed cellular cytotoxicity, and opsonization have been shown to play an important role in protection as well [2327].…”
Section: Discussionsupporting
confidence: 70%
“…Modified vaccinia Ankara was also shown to induce immune responses comparable with conventional VACV-based vaccines [14, 15]. Populations at an increased risk to receive first- and second-generation smallpox vaccines (ie, subjects with HIV-infection [16], atopic dermatitis [17], or immune-suppressive therapy [18], respectively) tolerated vaccination with MVA well and had a good immune response. To further evaluate MVA as a smallpox vaccine in at-risk individuals, this Phase II trial was conducted to compare the safety and immunogenicity of MVA in HIV-infected individuals and healthy controls.…”
mentioning
confidence: 99%
“…IMVAMUNE® is a modified vaccinia Ankara (MVA)-based smallpox vaccine, derived from MVA-597. IMVAMUNE ® is replicationrestricted to avian cells [4,5] and has an improved safety profile [6][7][8][9]; however, its efficacy against variola has not been tested. Both liquid and lyophilized formulations of IMVAMUNE® were tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Nt antibody titers of most volunteers peaked at 3 months, post-vaccination. On the other hand, Walsh et al reported that peak Nt antibody titers occurred on day 42 (14 days after second immunization) since they used 2 doses of MVA, a replication defective strain of vaccinia virus [21]. Persistence of protective Nt antibody was demonstrated for up to at least 6 months after primary vaccination in all participants.…”
Section: Discussionmentioning
confidence: 97%